2004
DOI: 10.1007/s00134-004-2503-2
|View full text |Cite
|
Sign up to set email alerts
|

Active transforming growth factor-β1 activates the procollagen I promoter in patients with acute lung injury

Abstract: Bronchoalveolar lavage fluid from ALI/ARDS patients activates procollagen I promoter, which is due partly to TGF-beta1. Activated TGF-beta1 may impact ARDS outcome independent of its effect on procollagen I activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 46 publications
2
56
0
1
Order By: Relevance
“…Consistent with this, the active pool of TGF-␤1 in patients with idiopathic pulmonary fibrosis, ranges from 17.6% in the upper lobe to 78.4% in the lower lobe (24). Active TGF-␤1 has been detected in BALs from patients with ARDS using bioactivity assays (6,12). However, the extent of activation was not determined in these studies.…”
Section: Discussionmentioning
confidence: 73%
“…Consistent with this, the active pool of TGF-␤1 in patients with idiopathic pulmonary fibrosis, ranges from 17.6% in the upper lobe to 78.4% in the lower lobe (24). Active TGF-␤1 has been detected in BALs from patients with ARDS using bioactivity assays (6,12). However, the extent of activation was not determined in these studies.…”
Section: Discussionmentioning
confidence: 73%
“…[10][11][12] Analogous observations have been reported in mechanically ventilated patients with ARDS. [13][14][15] Although large clinical trials have reassured clinicians that a low V t strategy 1 and judicious use of positive end-expiratory pressure (PEEP) 16,17 promote improved short-term outcomes in ARDS, including survival, their effects on early development of fibroproliferation remain unclear. Importantly, recent investigations using chest CT scanning have suggested that lung inhomogeneities typical of ARDS function as "stress raisers" that may locally increase the susceptibility to ventilatorinduced lung injury from externally applied pressure or volume, 18 highlighting the need to further delineate and characterize the eff ects of mechanical ventilation on ARDS pathophysiology.…”
Section: Subjects Examinedmentioning
confidence: 99%
“…It is now recognized that these processes occur simultaneously in the lungs of patients with ARDS (5). Previous studies have indicated that changes in various cytokines such as platelet-derived growth factor (PDGF) and transforming growth factor (TGF) are involved in these processes (6,7). Therefore, understanding the changes in the cytokines in these processes may provide possible opportunities for therapeutic intervention of ARDS.…”
Section: Introductionmentioning
confidence: 99%